Filling the gap: A thorough investigation for the genetic diagnosis of unsolved polyposis patients with monoallelic MUTYH pathogenic variants. Issue 12 (26th October 2021) - Dell'Elice, Anastasia; Cini, Giulia; Fornasarig, Mara; Armelao, Franco; Barana, Daniela; Bianchi, Francesca; Casalis Cavalchini, Guido Claudio; Maffè, Antonella; Mammi, Isabella; Pedroni, Monica; Percesepe, Antonio; Sorrentini, Italo; et al.
Abstract: Backgrounds: MUTYH ‐associated polyposis (MAP) is an autosomal recessive disease caused by biallelic pathogenic variants (PV) of the MUTYH gene. The aim of this study was to investigate the genetic causes of unexplained polyposis patients with monoallelic MUTYH PV. The analysis focused on 26 patients with suspected MAP, belonging to 23 families. Ten probands carried also one or more additional MUTYH variants of unknown significance. Methods: Based on variant type and on the collected clinical and molecular data, these variants were reinterpreted by applying the ACMG/AMP rules. Moreover, supplementary analyses were carried out to investigate the presence of other variants and copy number variations in the coding and promoter regions of MUTYH, as well as other polyposis genes (APC, NTHL1, POLE, POLD1, MSH3, RNF43, and MCM9 ). Results: We reclassified 4 out of 10 MUTYH variants as pathogenic or likely pathogenic, thus supporting the diagnosis of MAP in only four cases. Two other patients belonging to the same family showed a previously undetected deletion of the APC gene promoter. No PVs were found in the other investigated genes. However, 6 out of the 18 remaining families are still interesting MAP candidates, due to the co‐presence of a class 3 MUTYH variant that could be reinterpreted in the next future. Conclusion: Several efforts are necessary to fully elucidate the genetic etiology of suspected MAP patients, especially those with the most severe polyposis/tumor phenotype. Clinical data, tumor molecular profile, family history, and polyposis inheritance mode may guide variant interpretation and address supplementary studies. Abstract : The aim of this study was to investigate the genetic causes of unexplained polyposis patients with monoallelic MUTYH pathogenic variants. Clinical data, tumor molecular profile, family history, and polyposis inheritance mode may guide MUTYH variant interpretation and address supplementary studies of additional polyposis risk genes.